Expressive writing and relaxation: Psychological interventions for anxiety in individuals with substance use disorder (SUD) - Puspitosari, Warih Andan; Paramita, Cintya Al Zahra Wahyu; Wahyudi, Wahyudi (Science Midwifery, 2025)
Substance use disorder (SUD) is a global issue, with a high prevalence among laborers in Yogyakarta, Indonesia. Internal and environmental factors contribute to anxiety and disorientation, affecting mental health. This study aimed to evaluate the effectiveness of expressive writing therapy in reducing anxiety among laborers undergoing SUD rehabilitation. A quasi-experimental design with a non-equivalent control group was used, involving 36 outpatients at Dr. S. Hardjolukito Hospital, Yogyakarta, from June to November 2023. Participants were selected through purposive sampling based on specific criteria. The intervention group engaged in expressive writing and relaxation techniques, while the control group received standard treatment. Anxiety levels were measured using the HRS-A questionnaire before and after the three-month intervention. The Wilcoxon Signed Rank Test showed a significant reduction in anxiety in the intervention group (p = 0.000), while no significant change was observed in the control group (p = 0.513). These findings suggest that expressive writing therapy effectively reduces anxiety in laborers recovering from psychoactive substance use.